Nursing interventions in patients with type 2 diabetes mellitus that increase their self-care behaviors: systematic review - Aguayo-Verdugo, Natalia Valeska (2019)
The objective of this review was to identify nursing interventions that increase self-care behaviors in patients diagnosed with type 2 Diabetes mellitus. It is an integrative review where a search was made in the databases in SciELO, VHL, PUBMED and WOS, among September and December 2017, using the descriptors; diabetes mellitus type 2 AND self-care AND nursing care, in Spanish, English and Portuguese. Initially, 2,534 publications were identified and after the application of; filters, selection criteria and JADAD scale, the sample selected was 10 articles. In five of the studies the intervention had positive results with respect to self-care, of which four used strategies derived from psychology such as; motivational interview, theory of behavior change and problem solving. It is concluded that nursing professionals must deepen in the area of ​​psychology and formwork teams with these professionals, since people with diabetes mellitus type 2 need a change in behavior in the long term. Therefore, long-term interventions are also needed to achieve these changes and increase the quality of life of these patients.